2023
DOI: 10.1093/ofid/ofad148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sepsis on Death as Modified by Solid Organ Transplantation

Abstract: Background Patients with solid organ transplants (SOT) have an increased risk for sepsis compared to the general population. Paradoxically, studies suggest that SOT patients with sepsis may experience better outcomes compared to those without a SOT. However, these analyses used previous definitions of sepsis. It remains unknown whether the more recent definitions of sepsis and modern analytic approaches demonstrate a similar relationship. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Colbert et al [ 17 ] studied patients with inflammatory bowel disease and reported a decreased risk of hospital mortality in patients with Crohn's disease admitted for sepsis or septic shock (OR: 0.78; 95% CI 0.63–0.97). In solid organ transplant recipients hospitalized for sepsis, Donelly et al [ 12 ] reported a decreased in-hospital mortality (OR: 0.83; 95% CI 0.79–0.87) in a large retrospective study, and so did Kalil et al [ 18 ] at day 28 and day 90 in sepsis with bacteremia (HR: 0.22; 95% CI 0 0.09–0.54 and 0.43; 95% CI 0.20–0.89, respectively) or, more recently, Ackermann et al [ 13 ]. Finally, in line with our results, the single-centre retrospective study by Jamme et al [ 7 ], conducted in 309 immunocompromised patients admitted in the ICU for septic shock, reported an increased risk of hospital mortality in patients with solid tumour, but not in the subgroup of patients without malignancies (OR: 1.35; 95% CI 0.92–1.98), when compared to the general population.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Colbert et al [ 17 ] studied patients with inflammatory bowel disease and reported a decreased risk of hospital mortality in patients with Crohn's disease admitted for sepsis or septic shock (OR: 0.78; 95% CI 0.63–0.97). In solid organ transplant recipients hospitalized for sepsis, Donelly et al [ 12 ] reported a decreased in-hospital mortality (OR: 0.83; 95% CI 0.79–0.87) in a large retrospective study, and so did Kalil et al [ 18 ] at day 28 and day 90 in sepsis with bacteremia (HR: 0.22; 95% CI 0 0.09–0.54 and 0.43; 95% CI 0.20–0.89, respectively) or, more recently, Ackermann et al [ 13 ]. Finally, in line with our results, the single-centre retrospective study by Jamme et al [ 7 ], conducted in 309 immunocompromised patients admitted in the ICU for septic shock, reported an increased risk of hospital mortality in patients with solid tumour, but not in the subgroup of patients without malignancies (OR: 1.35; 95% CI 0.92–1.98), when compared to the general population.…”
Section: Discussionmentioning
confidence: 93%
“…Immunosuppression might modulate the host response to infection and may participate in higher mortality [ 7 ], reaching up to 70% six months after ICU admission for septic shock especially in patients with cancer [ 8 10 ]. Large retrospective studies showed an association between systemic disease and decreased 30-day mortality among ICU patients with septic shock [ 11 ], or a decreased in-hospital mortality in solid organ transplant patients hospitalized for sepsis [ 12 , 13 ]. Apart from these exceptions, information regarding the impact of long-term immunosuppressive treatment on the prognosis of patients admitted to the ICU for septic shock is scarce and only a few retrospective studies have been published, mainly including patients under chemotherapy [ 7 , 14 , 15 ], especially because this specific population is usually excluded from most clinical studies and therapeutic trials on sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, delayed graft function (DGF), which occurs in one in five patients receiving organ transplant, provides a favorable environment for sepsis because repeated biopsies of the transplanted organs are required ( 40 ). Patients with acute inflammatory and infectious diseases and those who have undergone DGF frequently develop sepsis, a systemic inflammatory disease with a remarkably high mortality rate ( 41 ). Furthermore, infections caused by injury can lead to sepsis.…”
Section: Acute Inflammatory and Infectious Diseases And Their Correla...mentioning
confidence: 99%